Single temperature liquefaction process at different operating pHs to improve ethanol production from Indian rice and corn feedstock. Issue 4 (21st April 2017) - Gohel, V.; Ranganathan, K.; Duan, G.
ABSTRACT: Conventional grain ethanol manufacturing is a high-temperature energy-intensive process comprising of multiple-unit operations when combined with lower ethanol recovery results in higher production cost. In liquefaction, jet cooking accounts for significant energy cost, while strong acid or base used for pH adjustment presents a safety hazard. A need is felt for sustainable ethanol manufacturing process that is less hazardous, consumes lower energy, and operates in a low pH range of 4.50–5.50. A single temperature liquefaction (STL) process that could efficiently operate at lower liquefaction temperature over a pH range of 4.50–5.50 was developed using rice and corn feedstock. Ethanol recovery witnessed at pH 4.5, 5.0, and 5.5 are 481.2 ± 1.5, 492.4 ± 1.5, and 493.6 ± 1.5 L MT −1 rice, respectively. Similarly, ethanol recovery witnessed at pH 4.5, 5.0, and 5.5 are 404.6 ± 1.3, 413.9 ± 0.8, and 412.4 ± 1.8 L MT −1 corn, respectively. The improvement in ethanol recovery is attributed to higher starch conversion by alpha-amylase even at pH as low as 4.50. Thus, the STL process operated at pH lower than 5.20 is poised to enhance sustainability by offering dual advantage of energy as well as chemical saving.